Small GTPase Rab8a-recruited Phosphatidylinositol 3-Kinase γ Regulates Signaling and Cytokine Outputs from Endosomal Toll-like Receptors - Wall, Adam A. (J Biol Chem, 2017)
LPS-mediated activation of Toll-like receptor 4 (TLR4) in macrophages results in the coordinated release of proinflammatory cytokines, followed by regulatory mediators, to ensure that this potentially destructive pathway is tightly regulated. We showed previously that Rab8a recruits PI3Kγ for Akt-dependent signaling during TLR4 activation to limit the production of the proinflammatory cytokines IL-6 and IL-12p40 while enhancing the release of the regulatory/anti-inflammatory cytokine IL-10. Here we broaden the array of immune receptors controlled by Rab8a-PI3Kγ and further define the Rab-mediated membrane domains required for signaling. With CRISPR/Cas9-mediated gene editing to stably knock out and recover Rab8a in macrophage cell lines, we match Akt signaling profiles with cytokine outputs, confirming that Rab8a is a novel regulator of the Akt/mammalian target of rapamycin (mTOR) pathway downstream of multiple TLRs. Upon developing a Rab8a activation assay, we show that TLR3 and 9 agonists also activate Rab8a. Live-cell imaging reveals that Rab8a is first recruited to the plasma membrane and dorsal ruffles, but it is retained during collapse of ruffles to form macropinosomes enriched for phosphatidylinositol 3,4,5-trisphosphate (PI(3,4,5)P(3)) and phosphatidylinositol 3,4-bisphosphate (PI(3,4)P(2)), suggesting that the macropinosome is the location where Rab8a is active. We pinpoint macropinosomes as the sites for Rab8-mediated biasing of inflammatory signaling responses via inducible production of anti-inflammatory cytokines. Thus, Rab8a and PI3Kγ are positioned in multiple TLR pathways, and this signaling axis may serve as a pharmacologically tractable target during infection and inflammation.